The Strategic Role of the Public Prosecutor’s Prosecution Plan in Imposing Severe Penalties for Child Abuse Crimes - Tri Andrisman; Maya Shafira; Muhammad Farid; Dita Trijayanti; Deni Achmad (Progressive Law Review, 2026)
Rentut has a strategic role for the prosecutor in prosecuting serious crimes against perpetrators of child molestation. Rentut functions as a juridical instrument that gives legitimacy to the demands, a victimological instrument that places child victims at the center of consideration, and a social-preventive instrument that affirms the state's attitude not to tolerate sexual crimes against children. In addition, Rentut also strengthened the consistency of prosecution between prosecutors so that it reflects the institutional policies of the prosecutor's office, not just the attitude of individual JPU. This study aims to find out and analyze the consideration of the Prosecution Plan (Rentut) by the Public Prosecutor (JPU) against the perpetrators of the crime of sexual abuse of biological children and the procedures carried out by the prosecutor in submitting a Rentut to the perpetrators of the crime of molestation of biological children. The main focus of this study is to understand how the prosecutor drafts criminal charges that are not only sentencing oriented, but also pay attention to the aspect of protecting child victims who have experienced deep trauma. The results of the study show that in compiling the charges, the prosecutor considers objective and subjective aspects as regulated in the Child Protection Law. The objective aspect includes the analysis of legal facts, evidence, and the application of the principle of lex specialis derogat lex generalis, while the subjective aspect includes moral, humanitarian, and socio-psychological factors on the victim. The procedure for preparing the Rentut is carried out systematically, starting from the collection of trial facts to the preparation of charges ratified by the Head of the District Attorney's Office. In the case of molestation of biological children, the prosecutor emphasized the imposition of punishment due to the betrayal of moral responsibility as parents. Keywords: Prosecution Plan, Public Prosecutor, Child Abuse, Child Protection